Evaluation of the underground economy in Quebec: A microeconomic approach - Bernard Fortin; Guy Lacroix; Dominique Pinard (Institute for the Study of Labor (IZA), 2010)
The main purpose of this paper is to estimate the size and the growth of Quebec's underground economy, and the corresponding loss of taxes for the government. Our approach is based on a method developed by Pissarides and Weber (1989) and extended by Lyssiotou et al. (2004). The basic hypothesis is that individuals can under-report their earnings from self-employment but not from paid work, from which taxes are directly deducted. We estimate a consumer demand system in which the marginal propensity to consume is allowed to vary with the two types of earnings. We next estimate the amount of self-employment earnings that are under-reported. From this estimate, we calculate the relative size of the underground economy in Quebec. We use data from Statistics Canada's Survey of Household Spending. According to our results, Quebec's underground economy amounted to 4.6% of GDP in 1997 and increased slightly to 5.7% in 2002. For the government, this represents approximately 3.3 billion in forgone taxes for the year 2002. This estimate is very close to those reported by Gervais (1994) and Fortin and Lacroix (2009) using very different estimation methods and data.
Keywords: D12; E26; H26; 330; underground economy; demand system; household behavior; generalized method of moments; tax evasion; income from self-employment